Inflammatory Rhabdomyoblastic Tumor: From a Nebulous Smooth Muscle Neoplasm to a Novel Skeletal Muscle Tumor Subtype - Michal, Michael (Surgical pathology clinics, 2024)
Inflammatory rhabdomyoblastic tumor is a recently introduced name for neoplasms currently included in the World Health Organization classification of soft tissue tumors under the rubric inflammatory leiomyosarcoma. Inflammatory rhabdomyoblastic tumor is an excellent example of how surgical pathologists working in conjunction with tumor biologists can greatly improve tumor classification to the benefit of patients. Over the last 28 years, understanding of this entity has undergone a fascinating evolution. This review serves as a summary of the latest findings in inflammatory rhabdomyoblastic tumor research and a diagnostic manual for the practicing surgical pathologist.
Keywords: nádory měkkých tkání; Leiomyosarcoma; Soft Tissue Neoplasms; kosterní svaly; Humans; nádory svalů; lidé; Muscle Neoplasms; leiomyosarkom; Smooth Muscle Tumor; Muscle, Skeletal; nádor z hladké svalové tkáně